Spindle Cell Lipoma Revisited: Common and Unusual Magnetic Resonance Imaging Findings in 54 Patients With New Observations. Issue 4 (July 2021) - Kumar, Rajendra; Lefkowitz, Robert A.; Agaram, Narasimhan P.; Amini, Behrang; Satcher, Robert L.; Wang, Wei-Lien
Abstract : Abstract: The aims of the study were to study demographic data of patients with spindle cell lipoma and describe a spectrum of magnetic resonance imaging features of the tumor.